Bibliometric Analysis of Research on Nutrition Interventions in Toddlers: A Focus on the Role of Mothers and the Impact of Supplementary Feeding Programs on Stunting Prevention - Vivin Ary Wijaya; Syamsul Arifin; Fauzie Rahman; Musafaah Musafaah; Adi Nugroho (Malahayati Nursing Journal, 2024)
ABSTRACT Stunting is a significant public health problem in many developing countries, including Indonesia. It affects not only children's physical growth but also their cognitive development and learning ability, ultimately impacting the quality of future human resources. Effective and timely nutrition interventions are essential to prevent stunting and ensure children reach their full potential. This bibliometric study aims to analyze the trends and focus of research related to nutritional interventions in children under five, with an emphasis on the role of mothers and the impact of supplementary feeding programs in stunting prevention. Using the Publish or Perish and VOSviewer applications, this study examined publications from Google Scholar between 2018 and 2024, identifying keywords, journal distribution by year, journal type, number of citations, and country of origin. The results revealed important findings regarding the central role of mothers, the importance of maternal nutrition knowledge, and complementary feeding practices in stunting prevention. The analysis identified four main clusters in the literature, showing a strong focus on the role of mothers, nutrition knowledge and complementary feeding practices. The study also highlighted the trend of increasing publications over the years and the dominant contribution of Indonesian researchers. Overall, the findings suggest that interventions targeting improved maternal knowledge and skills in complementary feeding are essential for effective stunting prevention. This study provides a comprehensive understanding of current research trends and identifies potential research gaps that can be further explored to improve the effectiveness of nutrition interventions and stunting prevention programs. Keywords: Stunting, Nutrition Interventions, Maternal Role, Complementary Feeding, Bibliometric Analysis